Administrative systems, situational leadership and decision-making in local economy management - Sanchez, Carlos Alberto Pacheco (2023)
Administrative systems and decision-making must be constantly studied in order to assess the strategic thinking of the administration with regard to its management and ability to achieve the competitiveness of organizations, however, the themes exposed in local economics are imprecise and little depth, therefore, the study knew the administrative system, the situational leadership style and the factors that affect the decision-making of a managerial type, with a quantitative-descriptive methodology, applying the questionnaire and the inquiry technique to 64 organized entrepreneurs in a sample stratified by economic sectors of Ocaña, it is concluded that in the business sector 70% have an administrative system of an authoritarian-coercive type, where more than 60% of service entities promote the participatory system, contrary to the sector of commerce and construction, finally, the timing and projection of the investment are important factors in the decision-making process.